A Potential Herbal Adjuvant Combined With a Peptide-Based Vaccine Acts Against HPV-Related Tumors Through Enhancing Effector and Memory T-Cell Immune Responses - Song, Ying-Chyi; Huang, Hui-Chi; Chang, Cherry Yin-Yi; Lee, Hui-Ju; Liu, Chuan-Teng; Lo, Hsin-Yi; Ho, Tin-Yun; Lin, Wu-Chou; Yen, Hung-Rong (Frontiers in Immunology, 2020)
Viral infection is associated with many types of tumorigenesis, including human papillomavirus (HPV)-induced cervical cancer. The induction of a specific T cell response against virus-infected cells is desired to develop an efficient therapeutic approach for virus-associated cancer. Chinese herbal medicine (CHM) has a long history in the treatment of cancer patients in Asian countries. Hedyotis diffusa Willd (Bai Hua She She Cao, BHSSC) is frequently used clinically and has been shown to inhibit tumor growth in vitro. However, in vivo data demonstrating the antitumor efficacy of BHSSC is still lacking. We showed that BHSSC induces murine and human antigen-presenting cell (APC) activation via the MAPK signaling pathway and enhances antigen presentation in bone marrow-derived dendritic cells (BMDCs) in vitro. Furthermore, we identified that treatment with BHSSC leads to improved specific effector and memory T cell responses in vivo. Variant peptide-based vaccines combined with BHSSC improved antitumor activity in preventive, therapeutic and recurrent HPV-related tumor models. Furthermore, we showed that rutin, one of the ingredients in BHSSC, induces a strong specific immune response against HPV-related tumors in vivo. In summary, we demonstrated that BHSSC extract and its active compound, rutin, can be used as adjuvants in peptide-based vaccines to increase immunogenicity and to bypass the requirement of a conditional adjuvant.